HUBUNGAN ANTARA MOTIVASI BELAJAR DENGAN HASIL BELAJAR IPS TERPADU SISWA KELAS VII SEMESTER GANJIL SMP PGRI 3 BANDAR LAMPUNG - Jaya, Wayan Satria (Lentera: Jurnal Ilmiah Kependidikan, 2012)
This study aims to obtain data on how far the relationship between motivation to learn with the learning outcomes of students in school. Method used is the correlation with quantitative approach. Can be said there is a positive relationship between motivation to learn with the learning outcomes of students in school by 14.11%. Therefore, to improve student learning outcomes in advance should increase learning motivation.